ANALISIS PERUBAHAN SUHU RUANGAN TERHADAP KENYAMANAN TERMAL DI GEDUNG 3 FKIP UNIVERSITAS JEMBER - Arlik Sarinda; Sudarti Sudarti; Subiki Subiki (JURNAL PEMBELAJARAN FISIKA, 2017)
Most people are often doing indoor activities that they demand indoor comfort to carry out better, calmer, and comfortable activities. This study aims to assess the change of room temperature towards time in Building 3 FKIP Jember University. The research was conducted in lecture room number 35C 201, 35B 203, 35B 101, and 35E 105Building 3 FKIP Jember University. The method used was adescriptive method. Data was analyzed using One-Way Anova using SPSS 22. The results of this study indicate that the ambient temperature in the room changes by time, in general it appears that the room temperatureat 06.00 until 17.00 had a p-value (significance) <0.05, which means there is a significant temperature difference. However, there are several variables that had a p-value (significance) ≥ 0.05 that means no significant temperature difference. The average temperature measurement shows that the highest average is in room 35C 201 (28,445oC), while the lowest is in 35E 105 (27,8oC). The average temperature of the four rooms scored above optimal comfort scale, which is 28.1oC, or higher. The lowest average temperature is obtained at 06.00 WIB with 26oC and the highest average is at 13.00 that reached 29,525oC Keywords: Thermal Comfort, Effective Temperature, Lecture Room